Literature Study Of Overview Of Castration Implementation In Pig - Mahani Willa; Tri Utami; Tarsisius C Tophianong (Jurnal Veteriner Nusantara, 2022)
Castration or orchiectomy is a surgical procedure performed on the testes, in the form of taking or cutting the testicles from the body. The purpose of this study was to determine the minimum age, castration technique and the advantages and disadvantages of castration in pigs. This literature study was obtained from searching and collecting various sources from Google Scholar by using the Mendeley application. Based on the results of the study, castration in pigs is more effective in cattle aged between 3-6 weeks of age because it affects growth, food conversion coefficient and carcass quality, and also metabolic and growth rate. The purpose of carrying out castration on pigs is to prevent unpleasant odors and tastes, support efforts to fatten male animals, produce high quality meat and reduce aggressive levels in male pigs. Castration techniques that can be used in pigs are open castration and immunocastration. The most common castration technique for pigs is the open castration technique or surgical castration technique. There is a new castration technique called immunocastration, which is a castration technique that involves injecting protein chemical compounds to induce the production of antibodies to gonadotropin-releasing hormone (GnRH). However, in this technique none of the chemical products used are licensed in the European Union and the consequences (consumer safety and animal welfare) have not been fully evaluated.